Intangibles : an empirical study on the valuation of biotechnology firms. - Loh, Aifeng. (2008)
This study examined the determinants of market value of biotechnology firms in the United States. Four intangible value drivers – Patents, Research & Development (R&D), Human Capital and Strategic Alliances were used to develop an empirical valuation model. We performed a regression of market values of biotech firms against individual variables that proxy for the intangible value drivers.